The correlation analysis of the cyclic casual process phase characteristics - Куц, Ю.В.; Щербак, Л.М. (Proceedings of National Aviation University (archive), 2005)
The technique of correlation functions of cyclic casual processes phase definition is offered. The technique is based on use of discrete Hilbert transformation, that allows to reduce the analysis time. The realization of the offered technique is considered on an example of the correlation functions analysis of a phase of a sine wave signal and gaussian noise additive mix.